The Influence of Coalescent Microbiotic Particles From Water and Soil on the Evolution and Spread of Antimicrobial Resistance - Baquero, F.; Coque, T.M.; Guerra-Pinto, N.; Galán, J.C.; Jiménez-Lalana, D.; Tamames, J.; Pedrós-Alió, C. (Frontiers in Environmental Science, 2022)
Water and soil contain a multiplicity of particulate material coated with bacterial populations and communities. Microbiotic particles are any type of small particle (measuring less than 2 mm) to which bacteria and other microbes attach, resulting in medium to long-term colonization. This study reviews the interactions of ecologically distant bacterial organisms on microbiotic particles in soil and water as a method for explaining the evolution and spread of antibiotic resistance traits. These particles include bacteria-bacteria aggregates, which can merge with particles from fungi, protozoa, phytoplankton, zooplankton, and biodetritus resulting from animal and vegetal decomposition, humus, mineral particles (clay, carbonates, silicates), and anthropogenic particles (including wastewater particles and microplastics). In turn, these complex particles can interact and coalesce. Natural phenomena (tides, currents, soil erosion/displacement, wind, rain) and anthropogenic activity (agriculture, waste-water management, mining, excavation/construction) favor the interaction and merging of microbiotic particles in soil and water, resulting in enhanced recombinant communities capable of exchanging genetic material, including antimicrobial resistance genes, particularly in antimicrobial-polluted environments. In this review, we propose that the worldwide spread of antimicrobial resistance might be related to the environmental dynamics of microbiotic particles, and we discuss possible methods for reducing this problem that threatens One Health and Global Health.